Reproductive ecology of Pisidium casertanum (Poli, 1791) (Bivalvia: Sphaeriidae) in Arctic lakes. (20th November 2018) - Bespalaya, Yulia; Joyner-Matos, Joanna; Bolotov, Ivan; Aksenova, Olga; Gofarov, Mikhail; Sokolova, Svetlana; Shevchenko, Alexander; Travina, Oksana; Zubriy, Natalia; Aksenov, Andrey; Kosheleva, Anna; Ovchinnikov, Denis
Abstract: We studied freshwater molluscan communities and the reproduction of the pea clam Pisidium casertanum in three types of Arctic lakes. The lakes differed in limnological features, both within and across lake type; although the composition of molluscan assemblages were similar, abundances varied considerably. Whereas the abundance of P. casertanum was not related to water macroion composition, shell length was negatively related to the concentrations of SO4 2−, Cl −, Mg 2+, Na + and Ca 2+ . The average number of embryos was positively correlated only with Mg 2+ content. Patterns in clam reproduction were influenced by differences in freezing times of the water body. The brooding mechanism involves asynchronous development and embryo release by the parent. We suggest that this follows a 'coin-flipping model' to increase breeding success in the exacting environment of Arctic lakes.